Tetrahydroimidazo[4,5-c]pyridine-Based Inhibitors of Porphyromonas gingivalis Glutaminyl Cyclase - Daniel Ramsbeck; Nadine Taudte; Nadine Jänckel; Stefanie Strich; Jens-Ulrich Rahfeld; Mirko Buchholz (MDPI AG, 2021)
Periodontitis is a severe yet underestimated oral disease. Since it is linked to several systemic diseases, such as diabetes, artheriosclerosis, and even Alzheimer's disease, growing interest in treating periodontitis has emerged recently. The major cause of periodontitis is a shift in the oral microbiome. A keystone pathogen that is associated with this shift is Porphyromonas gingivalis. Hence, targeting P. gingivalis came into focus of drug discovery for the development of novel antiinfective compounds. Among others, glutaminyl cyclases (QCs) of oral pathogens might be promising drug targets. Here, we report the discovery and structure-activity relationship of a novel class of P. gingivalis QC inhibitors according to a tetrahydroimidazo[4,5-c]pyridine scaffold. Some compounds exhibited activity in the lower nanomolar range and thus were further characterized with regard to their selectivity and toxicity.